HUBUNGAN KEJADIAN PUTTING SUSU LECET DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF - Nurul Agustin (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Abstract Mother’s milk exclusive is very important for baby’s grow, but there are many mother who can’t give her exclusive milk, the one of that is caused the mother’s hilt is chafed. It caused because the mother not understanding how to give her milk correctly, and if mother’s hilt is chafed, the mother became reluctant to give her milk and she will give a formula milk for her baby. The purpose of this research is for knowing the correlation incident of chafed hilt with the success of giving exclusive mother’s milk to the baby at the age 7-12 month in UPT Puskemas Jetis Mojokerto. The kind of this research is correlation with cross control phenomenological with the number of population counted 34 respondents. Samples was taken by Total Sampling, that is taken all of the population as sample counted 34 respondents .Instrument of data collecting was closed ended questioner and the process through editing, coding, scoring and tabulating. After that, data being analyzed by Crosstabs. So, H0 rejected and H1 accepted, it mean there is correlation incident of chafed hilt with the success of giving exclusive mother’s milk to the baby at the age 7-12 month in UPT Puskemas Jetis Mojokerto.